Morphology and chemistry of placer gold in the Bagrote and Dainter streams, northern Pakistan: Implications for provenance and exploration. (26th June 2018) - Alam, Masroor; Li, Sheng‐Rong; Santosh, M.; Yuan, Mao‐Wen
Abstract : The Bagrote and Dainter valleys in Gilgit Baltistan Pakistan, belonging to the Kohistan island arc and southwestern domain of the Karakorum metamorphic complex, respectively, are a location of regional placer gold mining. However, no in situ hydrothermal gold deposits have been discovered in this region. Here, we report the textural, morphological, and geochemical characteristics of placer gold from the stream sediments of the Bagrote and Dainter valleys with a view to trace the provenance. The morphological features of the studied gold grains indicate proximal source mineralization. The gold grains display a microtexture typical of mechanical abrasion rather than chemical activity. Their chemical composition of most of the grains from each stream falls in a restricted range (minor alloying elements mainly Cu) with high fineness (1, 000 Au/(Au + Ag)), suggesting derivation from a homogeneous source or limited number of mineralization types. The high Cu content of the gold grains from the Bagrote stream suggests that the gold here might be associated with previously undiscovered porphyry gold mineralization, whereas the Au–Ag–Hg alloys from the Dainter stream suggest a genetic linkage with undiscovered fault‐controlled auriferous veins of epithermal origin in the southwestern part of the Karakorum metamorphic complex. The chemical composition of both streams placer gold in triangular diagram in terms of Au–Ag–Cu shows all the gold grains from Dainter stream were derived from epithermal type of mineralization, and most of the plots of Bagrote stream fall on the domain of porphyry epithermal type of deposits which are also in consistent with a continental arc setting in the study area. The mechanically developed microtexture, homogeneous chemical composition in individual grains from core to rim, and absence of high fineness rims of the gold grains from both streams, suggest the absence of any supergene regrowth and direct transfer from the primary source through glacier to the fluvial system. The Gilgit Baltistan province, dominated by dry temperate climate and glacial environment having steep geomorphology, precluding any significant supergene processes such as silver leaching and addition of authigenic gold on detrital gold grains.